ANALISIS NILIA-NILAI PANCASILA PADA TRADISI BURDAH DI KECAMATAN MANDAH - Suharni, Syed Fajar YusFerry; Hambali; Haryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the form of actualization of Pancasila values ​​in the Burdah tradition carried out in Mandah District, Indragiri Hilir Regency. The Burdah tradition is part of a local culture that is religious and has an important role in the social life of the community. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation involving five main informants, namely the Head of the Riau Malay Customary Institution (LAMR) of Mandah District, sub-district government officials, the Head of Burdah, Burdah actors, and community leaders. The results of the study show that the values ​​of Pancasila are reflected in the implementation of the Burdah tradition, including the value of Divinity which is reflected in the opening of the event with the reading of the Al-Fatihah surah, the value of Humanity through equal treatment of all people present, the value of Unity in togetherness of the community in carrying out the tradition, the value of Deliberation when determining the time and place of implementation, and the value of Social Justice through the involvement of all levels of society. In addition to being a means of preserving culture, the Burdah tradition also plays a role as a medium for strengthening the nation's ideology. However, the involvement of the younger generation is still relatively low, so it is a challenge in the sustainability of this tradition.